If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5y + -5x) = 60 Reorder the terms: 3(-5x + 5y) = 60 (-5x * 3 + 5y * 3) = 60 (-15x + 15y) = 60 Solving -15x + 15y = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15y' to each side of the equation. -15x + 15y + -15y = 60 + -15y Combine like terms: 15y + -15y = 0 -15x + 0 = 60 + -15y -15x = 60 + -15y Divide each side by '-15'. x = -4 + y Simplifying x = -4 + y
| 8u+3v=-17 | | (2x+1)(x+3)=42 | | rz^5-6r-z^5+6=0 | | 8.17.8= | | 7=-2a | | -6(x-5)+5=35 | | y=6(25) | | 3(6z+-1)+-3(z+1)=11(z+1) | | -4*7*(-6)*5= | | m^3n-11m^2n^2+28mn^3=0 | | 1=6x | | c^2d^2+11cd+28=0 | | 9-(4n-4)=4-5n | | 8x^5+10x^4=4x^3+5x^2 | | (8.83-.33y)+4y=106 | | 2=x+6 | | 4x+5x-9=3x+x+6 | | 3(x-2)-4(x+1)= | | x=-1/2 | | x=-1/2 | | y^2-4y=4 | | 6y-4=2y+10 | | 3x+39=13x-37 | | 2a^2-12a+18=14 | | a-8=13 | | x^2+20x=9 | | h=25-9t | | 6(x+5)-(4x-5)= | | 9y-5=7+8y | | 240000=80x | | 6-(3x-3)-[2(-4x-1)]=-(-3x+2) | | 4y=15-y |